A novel approach for effective integration of new faculty leadership - Hastings NB; Centore LS; Gansky SA; Finzen FC; White, JM; Wong E; Marshall GW; Chung L; Kalenderian E (Dove Medical Press, 2018)
Natalie B Hastings,1 Linda S Centore,2 Stuart A Gansky,3 Frederick C Finzen,4 Joel M White,5 Eric Wong,6 Grayson W Marshall,7 Lisa Chung,3 Elsbeth Kalenderian3 1Division of Clinical General Dentistry, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA; 2Division of Behavioral Sciences & Community Dental Education, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA; 3Division of Oral Epidemiology & Dental Public Health, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA; 4Division of Prosthodontics, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA; 5Division of Preclinical Simulation, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA; 6Division of Endodontics, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA; 7Division of Biomaterials and Bioengineering, Department of Preventive and Restorative Dental Sciences, University of California, San Francisco (UCSF) School of Dentistry, San Francisco, CA, USA Purpose: We report on an accelerated and effective way of assimilating a new leader into a team at a large academic dental school department.Methods: At University of California, San Francisco (UCSF), a new Chair was recruited through a national search to lead its largest department in the School of Dentistry. Two months after arrival, the new Chair embarked on a process of leadership assimilation among her executive team, facilitated by a professional consultant. Within four weeks, team members participated in one-on-one interviews with the professional facilitator consultant and then completed the leadership assimilation questionnaire and returned it electronically to the facilitator. The facilitator then summarized all answers into themes and met with the team members without the Chair to debrief. Thereafter, the facilitator met with the Chair to discuss the major themes. Next, the Chair met with the team members in a facilitated session to discuss the results and negotiate a path forward.Results: Approximately half of the feedback described the “how” of leadership: comments on communication, building relationships, building trust, and understanding UCSF history. The remaining half described the “what”: comments on vision, strategy, and operations. Team members indicated that the first debriefing session was helpful to alleviate initial anxiety and to start building team spirit. The session with the Chair was perceived as open and fruitful in which team members were able to express their concerns and hopes for the Department, while the Chair showed commitment to the team and the communication process.Conclusion: Leader assimilation allows teams to share their expectations and anxieties with the new leader early in the relationship in an open way, before new habits and beliefs are formed. Conversely, for the leader, it effectively and efficiently allows a window into the team members’ thinking at a critical time period when otherwise first impressions occur. With a safe space created for open communication, the process allowed siloed individual division leaders to move toward a cohesive group while at the same time solidifying a commitment to the success of the new leader. Keywords: dental school, leadership, new leader assimilation, feedback, team, transition